You do £68.85 - £15.30= (the answer)
Then you do the answer of that divided by 0.85
That’s the answer because I couldn’t type it out! Hope it helped!
<h3><u>
Answer</u>
:</h3>
We know that,
![\dag\bf\:sin^2A=\dfrac{1-cos2A}{2}](https://tex.z-dn.net/?f=%5Cdag%5Cbf%5C%3Asin%5E2A%3D%5Cdfrac%7B1-cos2A%7D%7B2%7D)
![\dag\bf\:sin2A=2sinA\:cosA](https://tex.z-dn.net/?f=%5Cdag%5Cbf%5C%3Asin2A%3D2sinA%5C%3AcosA)
<u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u><u>_</u>
<u>Now, Let's solve</u> !
![\leadsto\:\bf\dfrac{sin^2A-sin^2B}{sinA\:cosA-sinB\:cosB}](https://tex.z-dn.net/?f=%5Cleadsto%5C%3A%5Cbf%5Cdfrac%7Bsin%5E2A-sin%5E2B%7D%7BsinA%5C%3AcosA-sinB%5C%3AcosB%7D)
![\leadsto\:\sf\dfrac{\frac{1-cos2A}{2}-\frac{1-cos2B}{2}}{\frac{2sinA\:cosA}{2}-\frac{2sinB\:cosB}{2}}](https://tex.z-dn.net/?f=%5Cleadsto%5C%3A%5Csf%5Cdfrac%7B%5Cfrac%7B1-cos2A%7D%7B2%7D-%5Cfrac%7B1-cos2B%7D%7B2%7D%7D%7B%5Cfrac%7B2sinA%5C%3AcosA%7D%7B2%7D-%5Cfrac%7B2sinB%5C%3AcosB%7D%7B2%7D%7D)
![\leadsto\:\sf\dfrac{1-cos2A-1+cos2B}{sin2A-sin2B}](https://tex.z-dn.net/?f=%5Cleadsto%5C%3A%5Csf%5Cdfrac%7B1-cos2A-1%2Bcos2B%7D%7Bsin2A-sin2B%7D)
![\leadsto\:\sf\dfrac{2sin\frac{2A+2B}{2}\:sin\frac{2A-2B}{2}}{2sin\frac{2A-2B}{2}\:cos\frac{2A+2B}{2}}](https://tex.z-dn.net/?f=%5Cleadsto%5C%3A%5Csf%5Cdfrac%7B2sin%5Cfrac%7B2A%2B2B%7D%7B2%7D%5C%3Asin%5Cfrac%7B2A-2B%7D%7B2%7D%7D%7B2sin%5Cfrac%7B2A-2B%7D%7B2%7D%5C%3Acos%5Cfrac%7B2A%2B2B%7D%7B2%7D%7D)
![\leadsto\:\sf\dfrac{sin(A+B)}{cos(A+B)}](https://tex.z-dn.net/?f=%5Cleadsto%5C%3A%5Csf%5Cdfrac%7Bsin%28A%2BB%29%7D%7Bcos%28A%2BB%29%7D)
![\leadsto\:\bf{tan(A+B)}](https://tex.z-dn.net/?f=%5Cleadsto%5C%3A%5Cbf%7Btan%28A%2BB%29%7D)
The question is:
Check whether the function:
y = [cos(2x)]/x
is a solution of
xy' + y = -2sin(2x)
with the initial condition y(π/4) = 0
Answer:
To check if the function y = [cos(2x)]/x is a solution of the differential equation xy' + y = -2sin(2x), we need to substitute the value of y and the value of the derivative of y on the left hand side of the differential equation and see if we obtain the right hand side of the equation.
Let us do that.
y = [cos(2x)]/x
y' = (-1/x²) [cos(2x)] - (2/x) [sin(2x)]
Now,
xy' + y = x{(-1/x²) [cos(2x)] - (2/x) [sin(2x)]} + ([cos(2x)]/x
= (-1/x)cos(2x) - 2sin(2x) + (1/x)cos(2x)
= -2sin(2x)
Which is the right hand side of the differential equation.
Hence, y is a solution to the differential equation.